Evaluation of Antibiotic use in Patients with Acute Respiratory Tract Infection (ARI) at Royal Prima Medan Hospital in 2023-2024 - Yobel Sitorus; Erida Novriani; Nerly Juli Pranita Simanjuntak (Jurnal Multidisiplin Sahombu, 2026)
Acute Respiratory Tract Infection is one of the infectious diseases frequently encountered in healthcare services. This stusy aims to assess antibiotic use in ARI patiets at Royal Prima Medan Hospital from January 2023 to August 2024 based on the appropriateness of drug selectin, and appropriateness of dosage. This study used a quantitave descriptive design with  a retrospective observational approach through data tracing of outpatient medical records. The sampel size was 135 patienst selescted using a percentage. The results showed that ARI patiens were predominantly male (57,8%) and aged 1-10 years(63,7%). The most prescribed antibiotic was cefixime (48,1%), followed by amoxicillin (17,0%), and cefadroxil (16,3%). Evaluation of antibiotic use showed that all patients met the criteria drugs, and appropriate dosage with a percentage of 100% each. This study indicates that antibiotic use in ARI patients at Royal Prima Medan Hospital is in accordance with the principles of rationel drug use.